Vehicle cabin roof thermal shield using phase change material - Nguyen , Vu Lan (Journal of Technical Education Science, 2016)
This paper presents amelioration for vehicle roofing design to improve its total thermal resistance. The key concept is to utilize phase change material properties to trap the heat from solar radiation and then release it back to the environment by means of the naturally favored external convection when the vehicle is running or during the nocturnal cycle. Experimental and numerical analyses have been conducted to compare the thermal performance of the new design and the normal roofing with different colors. A general mathematic equation system has also been derived for the thermal process through of the roof. Results show that the new design could effectively reduce the downward heat flow from the roof into the cabin. As a consequence, the cooling load of the cabin is significantly lower.